Atypical Antipsychotic Lumateperone Effects on the Adrenal Gland With Possible Beneficial Effect of Quercetin Co-administration - El-Haroun, Hala; Ewida, Suzy Fayez; Mohamed, Wael M. Y.; Bashandy, Manar Ali (Frontiers in Physiology, 2021)
Schizophrenia remains one of the most chronic and highly disabling mental disorders. Lumateperone is a recent FDA-approved atypical antipsychotic drug for the treatment of schizophrenia. However, the internal FDA pathologist raised concerns regarding pigment deposition associated with degeneration in different tissue in animal studies with lumateperone treatment. The adrenal gland may be implicated in lumateperone side effects, and quercetin may have the ability to fulfill this treatment gap. To prove this hypothesis, 40 male guinea pigs were used and divided into four groups; control, quercetin-treated, lumateperone-treated, and quercetin/lumateperone cotreated orally for 28 consecutive days. Behavioral forced swim (FST) and open field (OF) tests were done at the end of treatment. Retro-orbital blood samples were taken to assess hormones: adrenocorticotropic hormone (ACTH), cortisol, dehydroepiandrosterone acetate (DHEA), and aldosterone, along with an assessment of oxidative stress parameters: malondialdehyde (MDA), glutathione (GSH), and superoxide dismutase (SOD). Adrenal glands were extracted for histopathological assessment with H&E, Mallory trichome staining, immunostaining, and electron microscopy studies. Lumateperone-treated group showed a significant reduction in the activity in FST and OF with histopathological deterioration in adrenal secretory function and structure and increased expression of interleukin-6 (IL-6), CASPASE-3, collagen deposition, and decreased proliferating cell nuclear antigen (PCNA). Cytoplasmic vacuolation, pyknosis of the nuclei, increase in the lysosome, lipofuscin pigment, and cellular infiltration with diminishing in the number of secretory granules could all be observed in lumateperone-treated group. Coadministration of quercetin and lumateperone showed improvement of the previously deteriorated parameters. Quercetin had a prophylactic effect against lumateperone depressive-like effect on animal behavior and its possible adrenal damage. Graphical Abstract Conceptual framework for the proposed mechanism of action of coadministration of quercetin and lumateperone.